2013
DOI: 10.1016/j.acap.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Strict Smoke-free Home Policies Among Smoking Parents in Pediatric Settings

Abstract: Objective To examine strict smoke-free home policies among smoking parents assessed in pediatric offices. Methods We analyzed baseline parental survey data from 10 control practices in a national trial of pediatric office-based tobacco control interventions (Clinical Effort Against Second-hand Smoke Exposure, CEASE). We used logistic regression models with generalized estimating equations to examine factors associated with strict smoke-free home policies. Results Subjects were 952 parents who were current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
(68 reference statements)
1
11
1
Order By: Relevance
“…A partial domestic smoking ban was reported by 2.03% of our Changsha caregivers, which is lower than that noted in other studies [ 34 , 35 , 36 , 37 ]. Several factors may have contributed to this disparity.…”
Section: Discussioncontrasting
confidence: 82%
“…A partial domestic smoking ban was reported by 2.03% of our Changsha caregivers, which is lower than that noted in other studies [ 34 , 35 , 36 , 37 ]. Several factors may have contributed to this disparity.…”
Section: Discussioncontrasting
confidence: 82%
“…Having children was associated with having a smokefree home or any smokefree policy, which is consistent with at least some prior research (Ossip, et al, 2013), though in contrast to other research with college students (Berg, Lessard, et al, 2011). However, only about 20% of CC students with children reported a smokefree home policy.…”
Section: Discussionsupporting
confidence: 89%
“…For example, in 2012–2013, among combustible tobacco users, only about half (53.7%) reported smokefree homes and about one-third (34.2%) reported smokefree vehicles Kruger, et al, 2015). Presence of a young child in the home may attenuate this disparity (Berg, Lessard, et al, 2011; Nabi-Burza, et al, 2012; Ossip, et al, 2013), though at least one study found that presence of children was not associated with smokefree vehicles (Cheng, et al, 2015). Lower rates of smokefree home and/or vehicle policies have also been found for younger adults (ages 18–24; King, et al, 2013; Cheng, et al, 2015) relative to older groups, those with lower (vs. higher) education levels (Cheng, et al, 2015; King, et al, 2013; Kruger, et al, 2015), and those of lower (vs. higher) socioeconomic status (King, Hyland, Borland, McNeill & Cummings, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Data from a trial testing the Clinical Effort Against Secondhand Smoke Exposure (CEASE) (a pediatric office-based intervention that addresses parental smoking) in 2009-2011 revealed that most pediatricians in usual-care control practices were not asking or advising parent smokers about having smokefree homes and cars despite large proportions of parents not having strictly enforced smoke-free home and car policies (54% and 24% have strictly enforced smoke-free home and car policies, respectively). 30,31 Dissemination of previous research findings through national media, 32,33 Web sites, 34,35 and pediatricianfocused educational courses 36,37 encouraged pediatricians to advise parents to adopt strict smoke-free home and car policies to protect children from exposure to tobacco smoke. We aim to reexamine the prevalence of strictly enforced smoke-free home and car policies and additionally assess the prevalence of strictly enforced home and car policies that prohibit e-cigarette use among a 2017 sample of parents who visited pediatric practices randomly assigned to the control arm of the most recent (2015-2017) CEASE clinical trial.…”
mentioning
confidence: 99%